Relationship of Laser-Doppler-Flow and coronary perfusion and a concise update on the importance of coronary microcirculation in donor heart machine perfusion - Saemann, Lars; Großkopf, Anne; Hoorn, Fabio; Veres, Gábor; Guo, Yuxing; Korkmaz-İçöz, Sevil; Karck, Matthias; Simm, Andreas; Wenzel, Folker; Szabó, Gábor (Clinical hemorheology and microcirculation, 2021)
BACKGROUND: Machine perfusion (MP) is a novel method for donor heart preservation. The coronary microvascular function is important for the transplantation outcome. However, current research on MP in heart transplantation focuses mainly on contractil